The Impossible Trinity and capital flows in East Asia - Stephen Grenville (Asian Development Bank Institute (ADBI), 2011)
The Impossible Trinity doctrine still holds a powerful sway over policymakers, advisors (particularly the International Monetary Fund [IMF]) and academia. In East Asia over the past decade, however, most countries have been able to maintain open capital markets, monetary policy independence, and a fair degree of management over their exchange rates. This is because the Impossible Trinity model does not fit the actual circumstances very closely. Capital flows are dominated by factors other than interest differentials, external inflows have been successfully sterilized, the connection between base money and monetary policy settings is not close, and the authorities' management of the exchange rates has been aimed at keeping the rate close to the medium-term equilibrium, not susceptible to speculators. This is not to deny that there are difficult policy issues in the interaction between capital inflows, monetary policy, and the exchange rate. These interactions do in fact make good policymaking very challenging. The key problem is that the Wicksellian natural interest rate will differ quite substantially between developing and mature countries, presenting a structural problem rather than the cyclical problem envisaged in the Impossible Trinity. Rather than base the policy mind-set on the Impossible Trinity, it would be better to have in mind something along the lines of the Williamson band/basket/crawl and a notion of the fundamental equilibrium exchange rate.
Keywords: F21; F31; F32; 330; Mundell-Fleming-Modell; Kapitalmobilität; Geldpolitik; Wirkungsanalyse; Ostasien